Design of compact balanced ultra‐wideband bandpass filter with half mode dumbbell DGS. Issue 9 (4th April 2016) - Lu, Jiayuan; Wang, Jianpeng; Gu, Hui
Abstract : A new compact balanced ultra‐wideband (UWB) bandpass filter using half mode dumbbell defected ground structure (DGS) is presented. To realise the UWB response, the 'T' shape multiple‐mode resonator with short‐ended stub is employed. To achieve wideband common mode (CM) suppression and compact design simultaneously, the concept of half‐mode DGS is introduced in the two stacked microstrip layers. Afterwards, a balanced UWB filter is designed and measured for verifying the feasibility of the presented design method. The measured results match well with the expected results which indicate the proposed filter exhibits better than −30 dB CM suppression within the DM passband covering from 3.1 to 10.6 GHz.